2018
DOI: 10.1002/jcp.27529
|View full text |Cite
|
Sign up to set email alerts
|

Matrine is a novel inhibitor of the TMEM16A chloride channel with antilung adenocarcinoma effects

Abstract: Calcium‐activated chloride channels (CaCCs) are ion channels with key roles in physiological processes. They are abnormally expressed in various cancers, including esophageal squamous cell cancer, head and neck squamous cell carcinoma, colorectal cancer, and gastrointestinal stromal tumors. The CaCC component TMEM16A/ANO1 was recently shown to be overexpressed in lung adenocarcinoma cells and may serve as a tumorigenic protein. In this study, we determined that matrine is a potent TMEM16A inhibitor that exerts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 46 publications
0
31
0
1
Order By: Relevance
“…The three amino acid residues K384, R515, and R535 were located at the entrance of the TMEM16A protein near the pore outside in the cell membrane. The binding sites of a variety of TMEM16A inhibitors were compared, and we found that there are many inhibitors binding with TMEM16A in this region, including CaCC inh -A01, arctigenin, and matrine (Guo et al, 2019a;Guo et al, 2020b;Shi et al, 2020). Moreover, the binding sites of many inhibitors to TMEM16A included two same amino acid residues R515 and R535.…”
Section: Discussionmentioning
confidence: 85%
“…The three amino acid residues K384, R515, and R535 were located at the entrance of the TMEM16A protein near the pore outside in the cell membrane. The binding sites of a variety of TMEM16A inhibitors were compared, and we found that there are many inhibitors binding with TMEM16A in this region, including CaCC inh -A01, arctigenin, and matrine (Guo et al, 2019a;Guo et al, 2020b;Shi et al, 2020). Moreover, the binding sites of many inhibitors to TMEM16A included two same amino acid residues R515 and R535.…”
Section: Discussionmentioning
confidence: 85%
“…For example, oxymatrine impaired angiogenesis in mouse breast cancer in vitro and in vivo , by altering NF-κB pathway and VEGF signaling (34). Matrine inhibited migration and proliferation of mouse lung adenocarcinoma in vitro and slowed xenograft growth in vivo , by reducing expression of a calcium-dependent chloride channel shown to be upregulated in multiple cancer types (35, 36). Consistent with these findings, we found matrine added to the CKI minor fraction further impaired cancer cell migration (Figure 2C); however, in contrast, addition of oxymatrine to the CKI minor fraction did not affect the control of migration in any of the cell lines we tested.…”
Section: Discussionmentioning
confidence: 99%
“…Cl – channel inhibition Shikonin 6.5 [ 201 ] Preclinical Inhibition of CaCCs and Ca 2+ -activated basolateral K + channel Natural flavonoids (1 – Luteolin, 2 – Galangin, 3 – Quercetin and 4 – Fisetin) 4.5–15 [ 210 ] Preclinical Modulation of several ion channels. Inhibition of TMEM16A Matrine 27.94 [ 211 ] Preclinical Inhibition of TMEM16A Dehydroandrographolide ~20 [ 212 ] Preclinical Inhibition of TMEM16A. Anticancer activity Avermectins 0.15–1.32 [ 213 ] Preclinical Anthelmintic agents.…”
Section: Modulation Of Alternative (Non-cftr) Channels/transportersmentioning
confidence: 99%